2001
DOI: 10.1103/physrevlett.87.052001
|View full text |Cite
|
Sign up to set email alerts
|

Direct Observation of aρDecay of theD13(1520)Baryon Resonance

Abstract: The reaction gammap-->pi(+)pi(0)n has been measured at MAMI for photon energies up to 820 MeV. Invariant mass spectra of the particles in the final state (pi(+)n), (pi(0)n), (pi(+)pi(0)) have been determined for several bins of incident photon energy. Differences in pi(+)pi(0) and simultaneously measured pi(0)pi(0) invariant mass distributions are assigned to a rho branch of the D13(1520) nucleon resonance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 18 publications
2
35
0
Order By: Relevance
“…Particularly, the invariant-mass distributions measured by DAPHNE for γn → pπ − π 0 [8] in quasi-free kinematics off neutrons bound in the deuteron and by TAPS for γp → nπ 0 π + [28] supported this interpretation. The latter results were taken as evidence for a significant contribution from the D 13 (1520) → N ρ decay to the photoproduction of mixed charge pairs [28], which was subsequently also confirmed for the π + π − final state in electroproduction [26].…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…Particularly, the invariant-mass distributions measured by DAPHNE for γn → pπ − π 0 [8] in quasi-free kinematics off neutrons bound in the deuteron and by TAPS for γp → nπ 0 π + [28] supported this interpretation. The latter results were taken as evidence for a significant contribution from the D 13 (1520) → N ρ decay to the photoproduction of mixed charge pairs [28], which was subsequently also confirmed for the π + π − final state in electroproduction [26].…”
Section: Introductionmentioning
confidence: 71%
“…The first precise measurements of the total cross section and the invariant-mass distributions of pion-pion and pion-nucleon pairs for the π 0 π + final state for photoproduction off the proton in the second resonance region was done with the DAPHNE [27] and TAPS [28] experiments at the MAMI accelerator in Mainz. They revealed strong discrepancies with all available model predictions [1,28]. It was then suggested that the main effect was caused by the neglect of ρ contributions in the models (due to the relatively large mass of this meson, ρ contributions had been neglected in the second resonance region.)…”
Section: Introductionmentioning
confidence: 99%
“…During the last two decades, an extensive study of doublepion photoproduction for E γ < 1 GeV has been undertaken [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. The theoretical interpretation of the data in various isospin channels was carried out using different phenomenological analyses [15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…where the propagators S and ∆ are single-particle Green's functions for the nucleon and the pion, respectively, in complete analogy to Eq. (14). The structures of all equations here are similar: For a physical current, the four-divergence of the current, with propagators attached to its external legs, is expressed as a commutator ofQ with the corresponding (connected) Green's function.…”
Section: A Gauge Invariancementioning
confidence: 99%